2016
DOI: 10.1016/j.surfrep.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the air-cleaved mica surface

Abstract: The accepted image of muscovite mica is that of an inert and atomically smooth surface, easily prepared by cleavage in an ambient atmosphere. Consequently, mica is extensively used a model substrate in many fundamental studies of surface phenomena and as a substrate for AFM imaging of biomolecules. In this review we present evidence from the literature that the above picture is not quite correct. The mica used in experimental work is almost invariably cleaved in laboratory air, where a reaction between the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 231 publications
3
102
0
2
Order By: Relevance
“…Mica, a widely found layered clay mineral and one of the most prominent mineral surfaces due to its atomic flatness A. Abdelmonem: Direct molecular-level characterization of freezing and chemical inertness produced by perfect cleavage parallel to the 001 planes (Poppa and Elliot, 1971), was selected as a model surface in this study. However, the image of an inert and atomically smooth surface prepared by cleavage of muscovite mica in an ambient atmosphere is not quite correct (Christenson and Thomson, 2016). Surface analytical techniques found that the surface of muscovite mica cleaved in laboratory air, as is the case in this work, contains a water-soluble compound, potassium carbonate crystallites, which may cover a few tenths of a percent of the surface area (Christenson and Israelachvili, 1987).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Mica, a widely found layered clay mineral and one of the most prominent mineral surfaces due to its atomic flatness A. Abdelmonem: Direct molecular-level characterization of freezing and chemical inertness produced by perfect cleavage parallel to the 001 planes (Poppa and Elliot, 1971), was selected as a model surface in this study. However, the image of an inert and atomically smooth surface prepared by cleavage of muscovite mica in an ambient atmosphere is not quite correct (Christenson and Thomson, 2016). Surface analytical techniques found that the surface of muscovite mica cleaved in laboratory air, as is the case in this work, contains a water-soluble compound, potassium carbonate crystallites, which may cover a few tenths of a percent of the surface area (Christenson and Israelachvili, 1987).…”
Section: Introductionmentioning
confidence: 70%
“…However, the mobility of the potassium ions as potassium carbonate does not necessarily significantly affect any measurement of average surface properties as in the case of this work, and at high humidities the potassium will be widely dispersed across the surface. Those readers who are interested in more details on the nature of the mica surface in general and the air-cleaved mica surface in particular are referred to the review paper of Christenson and Thomson (2016) and papers cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Substrates were prepared by cleaving Muscovite mica, which generates a pristine surface that is atomically flat over large areas (23). These surfaces often feature a number of step edges, which can themselves support a range of defects.…”
Section: Resultsmentioning
confidence: 99%
“…Whist we cannot unambiguously determine the mechanism of the increased friction with water content, there is strong evidence in the literature of an effect particular to mica which we propose as most likely to underlie our observations. It is well established that mica cleaved in a humid atmosphere adsorbs water and CO2 which complex with the mica K + to form crystalline K2CO3 hydrates (44).…”
Section: R a F Tmentioning
confidence: 99%